SOCIODEMOGRAPHIC DETERMINANTS OF TURNOVER INTENTIONS AMONG NON-ACADEMIC STAFF IN STATEOWNED UNIVERSITIES IN IMO STATE - Onwuamaegbu, Promise O.; Nwagbo, Ifeoma L.; Abbas, Aminu A. (African Journal of Social and Behavioural Sciences, 2025)
This Study explored the sociodemographic determinates of turnover intentions among non-academic staff in state-owned universities in imo state. Three hypotheses were postulated and tested. One hundred and ninety-seven non-academic staff members were selected through a convenience sampling technique, which comprised 108 females and 89 males, out of which 107 were married and 90 were single. Their ages ranged from 29 to 53 years, with an average age of 35.23 years and a standard deviation of 9.24. The participants were administered with turnover intentions inventory (TOI). A cross-sectional survey design was adopted, analysis of variance (ANOVA) was used to analyse data collected. The results revealed that gender and age independently did not influence turnover intentions among non-academic staff at state-owned universities in imo state, while marital status influenced turnover intentions among non-academic staff at state-owned universities in imo state. This study addresses key gaps in turnover intentions and the need to adopt holistic approaches on how to reduce its effect on tertiary institutions. State government as a matter of urgency should strive to improve working conditions of non-academic staff through enhancing staff welfare and benefits, promoting job security, career progression and provide training and development opportunities.